Diabetes education in Mexico: patient and family - Pelcastre Neri, Aldo; Carranza-Ayala , Vanessa C. de (Mexican Journal of Medical Research ICSA, 2021)
Introduction. Despite the efforts to provide care for people with type 2 diabetes by conducting multiple intervention studies to educate people with diabetes mellitus, work still needs to be done to include the family as a strategy to improve disease control. Objective. A systematical review was made with the objective of analyzing educational interventions, implemented in adult people with diabetes mellitus type 2 in Mexico, including their family. Materials and Methods. Bibliographic search was made in CrossRef, Medline (PubMed), EBSCO, SCIELO and UAEH digital library. Results. From the nine articles found, seven mention the importance of the family receiving diabetes education. However, none of them mention the family in educational sessions as part of comprehensive management. Three articles mention the economic impact to the family as an out-of-pocket expense. Conclusions. Educational interventions in diabetes significantly improve the metabolic control of people with diabetes mellitus type 2, however, in Mexico there is no evidence of the inclusion of the family in such interventions, whose importance lies as support within the family system.